A Tibial Tubercle Fracture Masquerading as an Inferior Pole of the Patella Fracture. (20th January 2023) - Englert, E. Graham; Waheed, Muhammad; Saleh, Ehab
Abstract : Pediatric tibial tubercle fractures are uncommon injuries that most often occur in adolescent men. Patients will typically present with anterior knee pain with or without patella alta. This case report describes a tibial tubercle fracture in a 13-year-old man misidentified as an inferior pole patella sleeve fracture on physical examination and preoperative radiographs. The tubercle reduction was secured with cannulated screws while injury to the patellar tendon periosteal sleeve was repaired with suture anchors. This case highlights the utility of advanced imaging when the etiology of extensor mechanism disruption is unclear. Furthermore, it is imperative to set expectations with parents and guardians that the full extent of the injury may only be confirmed under direct visualization in the operating room because of the complexity of such injuries.